The development and validation of the Social Attributions for Mental Illness (SAMI) scale. - Leigh Huggard; Finiki Nearchou; Cliódhna O'Connor (PLoS ONE)
Existing measures of lay causal attributions for mental illness do not discriminate between the diverse array of social factors known to influence mental health. Moreover, while ample research has emphasised the negative stigma consequences of biological attributions, limited research investigates how different social attributions might relate to stigma attitudes. The study developed and validated a novel scale to measure lay social attributions for various categories of mental illness. Scale items were generated via data triangulation from an online qualitative survey, a rapid umbrella literature review, and a media analysis. An online survey was disseminated to 500 participants, who rated items' importance in causing four mental illness categories: anorexia nervosa, depression, schizophrenia, and post-traumatic stress disorder. Exploratory and confirmatory factor analysis identified and validated the factor structure of the Social Attributions for Mental Illness scale (SAMI) for each mental illness. Factors identified were life circumstances, violence/abuse, relational challenges, and sociopolitical turmoil. Tests of validity demonstrated good construct validity. This scale enables investigation of how social attributions may differ across populations and mental illness categories, and the consequences of such differences for attitudes and behaviour.